Assessing the Impact of Spraying an E. faecium Probiotic at Hatch and Supplementing Feed with a Triple-Strain Bacillus-Based Additive on BCO Lameness Incidence in Broiler Chickens - Khawla Alharbi; Anh Dang Trieu Do; Abdulaziz Alqahtani; Ruvindu Perera; Alexa Thomas; Antoine Meuter; Adnan Ali Khalaf Alrubaye (Animals)
Bacterial chondronecrosis with osteomyelitis (BCO) is a major cause of lameness in broiler chickens. This condition arises when bacteria from the gastrointestinal or aerosol tract migrate to infect bone microfractures, often exacerbated by rapid growth, reduced blood flow, and mechanical stress. As concerns about antibiotic resistance grow, probiotics have gained attention for their potential to improve gut health and reduce systemic bacterial load. This study evaluated the efficacy of a probiotic program comprising an Enterococcus faecium-based spray (2 × 109 CFU/bird at hatch) and a triple-strain Bacillus-based feed additive (B. subtilis 597, B. subtilis 600, and B. amyloliquefaciens 516 at 500 g/t feed from day 1 to 56), applied individually or in combination. A wire-flooring challenge model was used to simulate BCO transmission. A total of 1560 Cobb 500 broilers were randomly assigned to five groups: T1 (positive control), T2 (negative control), T3 (E. faecium spray only), T4 (Bacillus feed supplement only), and T5 (combined treatment). Lameness was evaluated daily from day 21 to 56 through clinical observation and necropsy. The challenge model was validated with >70% lameness in T1. All probiotic treatments significantly reduced lameness compared to T2 (p < 0.05): 35.4% in T3, 36.7% in T4, and 47.6% in T5. The combined treatment resulted in the statistically highest reduction in lameness incidence, indicating a synergistic rather than merely additive effect compared to individual treatments. These findings support the use of targeted probiotic strategies to reduce BCO lameness and enhance skeletal health and welfare in broilers.